Prospective Assessment of Social Network Quality among Depressed Mothers Treated with Brief Psychotherapy: The Social Network Quality (SNQ) Scales - Flores, Luis E. (Compr Psychiatry, 2017)
OBJECTIVE: Social relationships play important roles in emotional health, and are common targets of psychotherapeutic interventions. To better evaluate social relationship structure and function in the context of psychotherapy trials, this study introduces and psychometrically evaluates the Social Network Quality (SNQ) scales, which supplement the Social Network Index (SNI). The original SNI evaluates social network structure (i.e., extent of participation in diverse social roles and number of social relationships). The SNQ adds two social network quality scales evaluating levels of: (a) positivity/support, and (b) negativity/stress, within and across specific social roles. METHOD: Participants included 168 depressed mothers of psychiatrically-ill children participating in a psychotherapy treatment trial utilizing interpersonal therapy (IPT) and brief supportive therapy (BSP). The SNI, SNQ, and measures of social functioning and psychopathology were collected at baseline and at 3-month intervals over a one-year period. RESULTS: SNQ scores showed meaningful concurrent relationships with measures of social support and interpersonal distress, as well as incremental utility in explaining variance in relationship and mood outcomes above and beyond the SNI. SNQ scores also detected global and relationship-specific changes in social relationship quality following psychotherapy treatment. CONCLUSION: This report demonstrates that SNQ scales reliably assess psychotherapy-induced changes in relationship quality.